Pengajaran Tuhan Yesus Mengenai Berbahagia Dalam Matius 5:3-12 - Yohanes Enci Patandean (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2018)
Yohanes Enci Patandean, Preaching the Lord Jesus to be blessed in Matthew 5: 3-12. This article discusses the preaching of the Lord Jesus concerning of blessing in Matthew 5: 3-12 and analyzed there are three points to be analyzed, that is the understanding of blessing, blessing objects/goals and the reasons why should be blessed. The method that used is descriptive with a qualitative approach to the biblical text, and word analysis methods. In the text of Matthew 5: 3-12, Jesus teaches about blessed which includes the standard of living of the blessed people and the reasons why believers should be blessed. Jesus gives the preaching of blessing which includes the standard of living of a happy person is poor before God; mourning; gentle; hunger and thirst for righteousness; generous; sacred heart; bring peace; persecuted by righteousness; blemished and persecuted for Christ; and slandered all evil.